The significance of performing the OPGs in the detection of dentigerous cyst and mesiodentes - a case report - Jolanta Białkowska-Głowacka; Małgorzata Pińkowska-Prasał; Piotr Osica; Anna Janas-Naze (Kazimierz Wielki University, 2017)
The article describes a case of a maxillary dentigerous cyst with mesiodens in a 60-year-old patient, which was discovered accidentally on an OPG.